2020
DOI: 10.3346/jkms.2020.35.e327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Ventilation Strategy on Perioperative Atelectasis Assessed by Lung Ultrasonography in Patients Undergoing Open Abdominal Surgery: a Prospective Randomized Controlled Study

Abstract: Background: Protective mechanical ventilation using low tidal volume has been introduced to surgical patients to reduce the incidence of postoperative pulmonary complications. We investigated the effects of protective ventilation (PV) techniques on anesthesia-induced atelectasis identified via lung ultrasonography in patients undergoing abdominal surgery. Methods: A total of 42 adult patients who were scheduled for open abdominal surgery with an expected duration > 2 hours were included in the study. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…No hypoxemia was observed in either group. In patients who underwent open abdominal surgery in a previous study, the changes in the LUSs were moderately correlated with changes in PaO 2 /FiO 2 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No hypoxemia was observed in either group. In patients who underwent open abdominal surgery in a previous study, the changes in the LUSs were moderately correlated with changes in PaO 2 /FiO 2 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…B-lines are defined as hyperechoic vertical artifacts that originate from the pleural line, reach the bottom of the screen without fading and move synchronously with lung sliding [ 22 ]. Sets of at least three hyperechoic B-lines arising from the pleural line in one intercostal space are indicative of interstitial lung syndrome [ 23 ]. Each hemithorax was divided into six quadrants using two longitudinal lines (anterior and posterior axillary) and one axial line at the level of the nipples.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of this view is assessing anesthetized patients’ lungs in the supine position as our study did. Cho et al 34 also reported the difficulty of assessing postererobasal side of the lung. They tried using additional oblique scans along the intercostal space in the posterior region of the lung, but B-lines were still obscured by rib acoustic shadowing.…”
Section: Discussionmentioning
confidence: 99%